Combined approach in the treatment of comminuted lateral Hoffa fracture: a case report - Nastov, Nebojsha; Bekteshi, Labinot; Nikolovski, Andrej (Oxford University Press (OUP), 2024)
Abstract Coronal-plane intra-articular fractures of the femoral condyle (Hoffa fractures) are rare, and difficult to diagnose and treat. They mostly result as a consequence of high-energy trauma and are combined with concomitant fractures (patellar, tibia shaft) and/or soft-tissue damage. A plain X-ray can miss the diagnosis initially and therefore computerized tomography scan is recommended, which can also help in the preoperative planning. The vast majority of these fractures are unicondylar (mostly lateral condyle fractured). The approach for their treatment can be anterior or posterior. In cases of fracture comminution, much more mutilant approaches with osteotomy have been described. A combined two-stage approach can be used to obtain anatomical reduction and fixation of all the fragments. We present a case of a 46-year-old male patient with comminuted lateral Hoffa fracture treated with a combined approach (extended posterior approach to the proximal tibia and lateral parapatellar) in a time interval of one month.
Keywords: Hoffa fracture; comminution; unicondylar; combined approach